Effect of Potassium on Boro-fallow-t. Aman cropping pattern in old Brahmaputra floodplain soil of Bangladesh - Islam, MR; Afroz, H; Pervin, R; Ansari, F; Rahman, MH (SAARC Journal of Agriculture, 2015)
Field experiment was conducted at the Bangladesh Institute of Nuclear Agriculture (BINA) farm, Mymensingh during 2010-11 to 2011-12 to investigate the effect of different levels of K on Boro-Fallow-T. Aman cropping pattern in Old Brahmaputra Floodplain Soil of Bangladesh. There were four treatments for the first crop (Boro rice): T1 (Control), T2 (50% NPKS), T3 (75%NPKS) and T4 (100% NPKS). The 100% NPKS rates were recommended on the basis of soil test values. T4 treated plot of each block was further split into seven sub-plots to represent seven treatments (T4.1 to T4.7) for the second crop of T. Aman in the sequence. The results reveal that the grain yield of boro rice varied from 2.33 to 6.00 t ha-1 of which the highest yield was recorded with the application of 100% NPKS (T4) and the lowest with T1 (control). The effect of boro rice straw removal or incorporation was clearly visible on the following crop, T. Aman rice. The highest grain and straw yields of T. Aman were obtained with T4.4 treatment, where 75% straw was removed and 25% straw incorporated with soil. The lowest yield was obtained with the control crop without fertilizer or straw residues. The NPKS uptake by T. Aman rice and benefit : cost ratio supported the dominant performances of T4.2 (100% NPS + 50% K + 25% boro rice straw removed). The results suggested that it is possible to reduce K mining from soils as well as to reduce the rate of K fertilizer application, substituting by incorporation of rice straw residues in soil system. DOI: http://dx.doi.org/10.3329/sja.v12i2.21924 SAARC J. Agri., 12(2): 123-133 (2014)